Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/nl9012216
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Beam-Induced Deposition of Platinum from a Liquid Precursor

Abstract: We demonstrate here the first focused electron-beam-induced deposition (EBID) of nanostructures using a liquid precursor. We have deposited sub-50 nm platinum (Pt) wires and dots from a dilute, aqueous solution of chloroplatinic acid. Existing EBID processes rely on the electron-beam stimulated decomposition of gaseous precursors; as a result, the deposits are highly contaminated (up to 75 at. % carbon or 60 at. % phosphorus for Pt processes). In contrast, we show that deposition of platinum by electron-beam r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 20 publications
5
79
1
Order By: Relevance
“…[19] Higher material purity has been demonstrated compared to the gas phase EBID. [15,16] With TEM/ STEM, the deposition of Pt, Ag, and PbS has been reported, [14,[20][21][22] and in this year, Grogan et al demonstrated direct writing of nanoscale Au letters using this technology. [23] Compared to the in situ SEM approach, the TEM approach offers higher in situ imaging spatial resolution (can be up to atomic resolution in liquid), and thus provides a better tool for in situ study of the material growth behaviour during EBID.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[19] Higher material purity has been demonstrated compared to the gas phase EBID. [15,16] With TEM/ STEM, the deposition of Pt, Ag, and PbS has been reported, [14,[20][21][22] and in this year, Grogan et al demonstrated direct writing of nanoscale Au letters using this technology. [23] Compared to the in situ SEM approach, the TEM approach offers higher in situ imaging spatial resolution (can be up to atomic resolution in liquid), and thus provides a better tool for in situ study of the material growth behaviour during EBID.…”
Section: Introductionmentioning
confidence: 97%
“…[9] Based on these developments, liquid phase electron beam induced deposition (LP-EBID) is now made possible. [8,14,15] Hastings et al [15][16][17][18] have demonstrated Pt and Au nano dot and nano wire deposition with LP-EBID in scanning electron microscope (SEM) (polyimide membranes were also used). The deposition of silver nano aggregates has also been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This liquid-phase electron beam induced deposition is an intriguing technique for generating micro-and nanowires with controlled sizes and patterns without the use of a mask and has been explored in this and other materials. 40,41 We now briefly discuss the limitations of the model. The data used in developing equations (4) and (5) were measured for low dose-rate irradiation (< 1000 Gy s ⁄ ).…”
mentioning
confidence: 99%
“…The minimum size of the deposit is similarly expected to be strongly dependent on the beam size and energy as well as on the ion supply. The smallest feature sizes demonstrated in optimized lithography tools for electron beam–induced deposition in liquids are in the 20- to 30-nm range ( 31 ); in STEM, feature sizes down to 40 nm have been demonstrated ( 32 ). The crystal size is controllable because the total number of ions can be specified, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%